Potential Physiological Parameters to Indicate Inner States in Dogs: The Analysis of ECG, and Respiratory Signal During Different Sleep Phases - Bálint, Anna; Eleőd, Huba; Körmendi, János; Bódizs, Róbert; Reicher, Vivien; Gácsi, Márta (Frontiers in Behavioral Neuroscience, 2019)
The sleeping activity of family dogs has been studied increasingly in the past years. Recently, a validated, non-invasive polysomnographic method has been developed for dogs, enabling the parallel recording of several neurophysiological signals on non-anesthetized family dogs, including brain activity (EEG), eye movements (EOG), cardiac (ECG) and respiratory activity (PNG). In this study, we examined the ECG (N=30) and respiratory signals (N=19) of dogs during a 3-hour sleep period in the afternoon, under laboratory conditions. We calculated four time-domain heart rate variables (mean heart rate (HR), SDNN, RMSSD, pNN50) from the ECG and the estimated average respiratory frequency from the respiratory signal. We analyzed how these variables are affected by the different sleep-wake phases (wakefulness, drowsiness, NREM, REM) as well as the dogs’ sex, neutered status, age and weight. We have found that the sleep-wake phase had a significant effect on all measured cardiac parameters. In the wake phase, the mean HR was higher than in all other phases, while SDNN, RMSSD and pNN50 were lower than in all other sleep phases. In drowsiness, mean HR was higher compared to the NREM and REM phases, while SDNN and RMSSD was lower compared to the NREM and REM phases. In REM, SDNN and RMSSD was higher than in NREM. However, the sleep-wake phase had no effect on the estimated average respiratory frequency of dogs. The dogs’ sex, neutered status, age and weight had no effect on any of the investigated variables. This study represents a detailed analysis of the cardiac and respiratory activity of dogs during sleep. Since variations in these physiological signals reflect the dynamics of autonomic functions, a more detailed understanding of their changes may help us gain a better understanding of the internal/emotional processes of dogs in response to different conditions of external stimuli. As such, our results are important since they are directly comparable to human findings and may also serve as a potential basis for future studies on dogs.